1999
DOI: 10.2337/diacare.22.10.1655
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative scale of acanthosis nigricans.

Abstract: We have developed a scale for AN that is easy to use, has high interobserver reliability in Mexican Americans, and correlates well with fasting insulin and BMI. This scale will permit longitudinal and cross-sectional evaluation of AN and will permit the evaluation of AN as a trait in genetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
231
1
10

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(252 citation statements)
references
References 0 publications
10
231
1
10
Order By: Relevance
“…Insulin resistance is thought to be a major factor in the pathophysiology of type 2 diabetes in both adults and children (4 -6). Acanthosis nigricans (AN), a skin disorder characterized by hyperpigmentation, hyperkeratosis, and papillomatosis, is a clinical marker that has been linked to surrogate markers of insulin resistance in adults (7,8) and adolescents (9), but only a few studies have explored the relation between directly measured insulin sensitivity (S i ) and AN in children (10 -12). Studies in adults have suggested that those with AN have elevated fasting insulin levels (13,14).…”
Section: Diabetes Care 27:1412-1416 2004mentioning
confidence: 99%
“…Insulin resistance is thought to be a major factor in the pathophysiology of type 2 diabetes in both adults and children (4 -6). Acanthosis nigricans (AN), a skin disorder characterized by hyperpigmentation, hyperkeratosis, and papillomatosis, is a clinical marker that has been linked to surrogate markers of insulin resistance in adults (7,8) and adolescents (9), but only a few studies have explored the relation between directly measured insulin sensitivity (S i ) and AN in children (10 -12). Studies in adults have suggested that those with AN have elevated fasting insulin levels (13,14).…”
Section: Diabetes Care 27:1412-1416 2004mentioning
confidence: 99%
“…A number of studies (15)(16)(17)(18)(19)(20)(21) suggest that overweight status in AfricanAmerican children and adolescents is associated with insulin resistance and that children may be developing IRS early in life. Establishing the relation between obesity and the risk factors of IRS and insulin resistance in young children Ͻ10 years of age will aid in understanding the disease course of the development of type 2 diabetes.…”
mentioning
confidence: 99%
“…Other studies have also shown that there are many cases with AN in the knuckles without AN in the neck or other classical sites. 17 , 24-26 Consequently, AN in the knuckles should be considered as a classic, highly prevalent, difficult-to-hide clinical sign that arises a caution of compensatory hyperinsulinemia secondary to IR.…”
Section: Discussionmentioning
confidence: 99%
“…24 A fasting blood sample was taken for plasma glucose and serum insulin levels to determine HOMA-IR index. 45 Also, a standardized close-up photography of the neck, axillae, elbows, and knuckles was taken.…”
Section: Methodsmentioning
confidence: 99%